2018
DOI: 10.1111/ctr.13211
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of intraoperative cytokine adsorption on outcome of patients undergoing orthotopic heart transplantation—an observational study

Abstract: Intraoperative CA treatment was associated with reduced vasopressor demand and less frequent renal replacement therapy with a favorable tendency in length of mechanical ventilation and ICU stay. CA treatment was not linked to higher rates of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 37 publications
4
53
1
2
Order By: Relevance
“…Although the difference between the groups did not reach statistical significance, these results at least provide some physiological background that vasodilatation, most likely due to the overwhelming effects of pro-inflammatory cytokines, was better controlled in the treated group. This finding is in accordance with previously reported data, both in case series and in recent clinical studies [25]. It is also important to note, that the most profound effects were observed during the first 12 h of treatment, which has not been reported before.…”
Section: Clinical Effectssupporting
confidence: 94%
“…Although the difference between the groups did not reach statistical significance, these results at least provide some physiological background that vasodilatation, most likely due to the overwhelming effects of pro-inflammatory cytokines, was better controlled in the treated group. This finding is in accordance with previously reported data, both in case series and in recent clinical studies [25]. It is also important to note, that the most profound effects were observed during the first 12 h of treatment, which has not been reported before.…”
Section: Clinical Effectssupporting
confidence: 94%
“…Similarly, a prospective randomized control trial in patients who underwent cardiac surgery also found no significant impact on cytokine concentrations although this study was not performed in sepsis [76]. In a recent propensity-matched retrospective study on 32 patients, the influence of intraoperative cytokine adsorption on the perioperative vasoplegia, inflammatory response and outcome during orthotopic heart transplantation was investigated [77]. Intraoperative CytoSorb treatment was associated with reduced vasopressor demand and less frequent RRT with no difference in length of mechanical ventilation and ICU stay [78].…”
Section: Does the Use Of Cytosorb Haemoadsorption Therapy In Patientsmentioning
confidence: 99%
“…3]. Less vasopressor was needed during the operation, and fewer renal replacement therapy implemented after the surgery in patients who used Cytosorb connected to the cardiopulmonary by-pass [23,24]. In a study performed by Gleason et al, patients with haemoadsorption had a significantly lower free haemoglobin and activated complement serum concentrations [25].…”
Section: State Of Knowledgementioning
confidence: 99%